Failure of the Law to Grant Access to Legal Abortion in Chile - Daniel F.M. Su?rez-Baquero; Ilana G. Dzuba; Mariana Romero; C. Finley Baba; M. Antonia Biggs (Mary Ann Liebert, 2024)
Introduction: In 2017, Chile decriminalized abortion on three grounds: (i) if the pregnant person's life is at risk, (ii) fetal nonviability, and (iii) rape or incest. This multicase study explores the experiences of pregnant people legally entitled to but denied access to legal abortion in Chile. Methods: Through a snowball sampling approach, we recruited adult Chilean residents who sought, were eligible for, and were denied a legal abortion after September 2017. We conducted semistructured interviews with participants to explore their experiences in seeking and being denied legal abortions. We recorded and transcribed the interviews, then coded and analyzed the transcriptions to identify common themes. Results: We identified four women who met the eligibility criteria. The interviews revealed five common themes in their experiences: (i) disparate levels of social support in accessing abortion, (ii) abundant access barriers, (iii) forced pregnancy, (iv) abortion stigma, and (v) a failure of the law to provide access to abortion. Discussion and Health Equity Implications: Although the 2017 law expanded legal access to abortion in Chile, significant barriers remain. Compounded with social stigma, and the socioeconomic disparities in abortion access, pregnant people continue to face insurmountable obstacles in obtaining legal abortions, even when their lives are at risk and the pregnancy is not viable. The state must prioritize equity of access to legal abortions. Future studies should continue to explore the challenges people face accessing legal abortion care to inform strategies to ensure people are able to obtain the quality care that they are legally entitled to.